Non-Nephrotic Proteinuria in Children: A Review - Akhavan Sepahi, Mohsen (Journal of Pediatric Nephrology, 2019)
Proteinuria is defined as an increased abnormal urinary excretion of proteins. In normal conditions, few proteins are lost through the urine. Proteinuria is a problem and dilemma in pediatric practice. Non- nephrotic proteinuria is described and its follow-up is discussed in the following. Keywords: Proteinuria; Non-nephrotic proteinuria; Nephrotic syndrome; Child.